ANALYSIS OF DEUTSCHE WELLE FRAMES ON NEWS ABOUT HANAU ATTACK - DAVID RANDY; NAWIROH VERA (Metakom, 2020)
The high frequency of terror attacks that occurred in several countries has an impact on the pattern of media coverage. Previous studies indicate a standardization and formulation of media in constructing the reality about the attacks. The broad reach of the mass media potentially makes the reality framed by media affect the public's understanding of the issue significantly. This research uses critical paradigm with a qualitative approach, aims to examine and explore the constructed reality of Hanau attacks by analyzing the audio-visual content using Edelman method. Theories used are the theory of media construction of reality and news frame theory. The results indicate a similarity between the reality built by Deutsche Welle on the news about the Hanau attack and the reality about attack (in general) which is constructed by US media, such as Fox News Channel. There are some indications that Deutsche Welle producers are a bit resistance in using the word terror and terrorist on covering Hanau attack, apart from the official statement of the federal prosecutor's office that categorizes the case as terrorism.